Determining the dominant corporate entrepreneurship model in Mutare based private schools and implications for business growth. - Tachi, A (BUSE, 2023)
This dissertation investigates the dominant corporate entrepreneurship model in Mutare-based private schools and its implications for growth. A sad indicator that there is a missing link between the use of corporate entrepreneurship that can drive private schools' education and private schools' growth is the current situation of comatose private school survival in emerging nations like Zimbabwe. The study used exploratory research approach, outlining the study aspects and facts that were already available. Exploratory research investigates research questions that have not been studied in depth. The study also adopted a case study approach. Which in this case required a group of schools to be part of the population. The study employed mixed methods. The study measured quantitative data on the dominant model of corporate entrepreneurship approach and on assessing the implications of the adoption of each model of corporate entrepreneurship in the private schools in Mutare. The study demonstrated that, in accordance with the opportunistic model, it significantly facilitated the identification of new markets in business, as confirmed by the respondents. Schools need to make use of the enabler model of entrepreneurship since the study showed that it is the dominant model in line with schools. The researcher also recommends that there is need to transform knowledge into innovation and embark on entrepreneurial activities in schools. Also the research recommends need to embrace the enabler model since it encourages growth, expanding market base and the identification of new markets.
Keywords: corporate entrepreneurship; dominant models; exploratory research; private schools; Mutare; Zimbabwe